REGRESI LOGISTIC PARITAS DAN HIPERTENSI TERHADAP KEJADIAN SOLUSIO PLASENTA - Linda Yanti; Dyah Arum (Viva Medika, 2009)
Placental abruption is actually more dangerous than placenta previa for pregnant women and janinya. Placental abruption is the separation of the placenta from normalimplementation before birth janin.Faktor cause placental abruption is unknown, but thecondition of placental abruption can be attributed to the following matters, namely highblood pressure in the mother, maternal age or at high enough parity, smoking, poor nutrition, chorioamnionitis, blunt trauma to the maternal abdomen, previous history of placentalabruption, the increase in volume and uterine size. This study To determine the relationshipbetween parity and history of hypertension in women giving birth with the incidence ofabruption plasentadi Hospital Dr. Margono Soekarjo 2009. This study researchers used acorrelation study with cross sectional approach. Samples using quota sampling. Sample thisstudy were all birth mothers of 100 respondents 37 mothers who experienced abruption and63 who had not had abruption.Results: From the results, most have parity primiparas as many as 38 respondents (38%), didnot have a history of hypertension as many as 60 respondents (60%). There is a relationshipbetween maternal parity on the incidence of placental abruption (χ² count> χ² table (18.919>5.991)), there is a relationship between a history of hypertension on the incidence ofmaternal placental abruption (χ² count> χ² table (26.605> 3.841)). There is a relationshipbetween parity and history of hypertension in women giving birth with the incidence ofabruption plasentadi Hospital Dr. Margono Soekarjo in 2009 (χ² count> χ² table). Keywords: Parity, hypertension, placenta abruption